Advances in the treatment of pediatric obsessive–compulsive disorder: rationale and design for the evaluation of D-cycloserine with exposure and response prevention. (August 2012) - McGuire, Joseph F; Lewin, Adam B; Geller, Daniel A; Brown, Ashley; Ramsey, Kesley; Mutch, Jane; Mittelman, Andrew; Micco, Jamie; Jordan, Cary; Wilhelm, Sabine; Murphy, Tanya K; Small, Brent J; et al.
SUMMARY  Exposure-based cognitive-behavioral therapy and serotonin reuptake inhibitor medications are efficacious treatment options for the management of pediatric obsessive–compulsive disorder. Despite established efficacy, many youths receiving either therapy remain symptomatic after acute treatment. Regardless of the rationale for persistent symptoms, a clear need emerges for treatment options that restore functioning efficiently to symptomatic youths. One innovative approach builds upon the identified role of NMDA receptors in the fear extinction process. Instead of breaking existing connections during fear extinction, new associations develop that eventually predominate over prior associations. Recent investigations have explored augmenting exposure-based cognitive-behavioral therapy with the NMDA partial agonistD -cycloserine, with preliminary results demonstrating expedited treatment gains and moderately larger effects above exposure and response prevention therapy alone. A large randomized clinical trial is underway to evaluate the efficacy and efficiency of this therapeutic combination in pediatric obsessive–compulsive disorder. Results from this trial may translate into improved management practices.